2020
DOI: 10.22373/p-jpft.v1i2.6619
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Inkuiri Terbimbing Dengan Pendekatan Multirepresentasi Terhadap Peningkatan Penguasaan Konsep Fisika Siswa Sma

Abstract: Penelitian ini dilatar belakangi oleh tidak maksimalnya pembelajaran fisika dengan pendekatan multirepresentasi yang diterapkan di SMA Negeri 15 Bandung. Tujuan penelitian ini adalah untuk menganalisis pengaruh signifikan model pembelajaran inkuiri terbimbing dengan pendekatan multirepresentasi terhadap peningkatan penguasaan konsep fisika siswa. Metode penelitian yang digunakan adalah preexperimental design dengan desain eksperimen one group pretest-posttest design. Sampel dalam penelitian ini adalah siswa-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Tri Isti Hartini, Martin / The Influence of Multiple Representation-Based Online Lectures Using Geogebra on Understanding of Students' Thermodynamics Concepts During the Covid-19 Pendemic Period concepts in the covid 19 pandemic. The results of this study are in line with the results of research by (Abdurrahman, Liliasari, Rusli, & Waldrip, 2015), (Hasbullah et al, 2019) and (Kurniasih et al, 2020) who found that the use of various representations in physics learning was effective for improving students' understanding of concepts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Tri Isti Hartini, Martin / The Influence of Multiple Representation-Based Online Lectures Using Geogebra on Understanding of Students' Thermodynamics Concepts During the Covid-19 Pendemic Period concepts in the covid 19 pandemic. The results of this study are in line with the results of research by (Abdurrahman, Liliasari, Rusli, & Waldrip, 2015), (Hasbullah et al, 2019) and (Kurniasih et al, 2020) who found that the use of various representations in physics learning was effective for improving students' understanding of concepts.…”
Section: Discussionsupporting
confidence: 89%
“…Empirical research related to the application of multiple representations in improving students' understanding of concepts has been done before. The results of research by (Hasbullah, Halim, & Yusrizal, 2019) and (Kurniasih, Novia, & Jauhari, 2020) show that the use of various representations in physics learning can improve students' conceptual understanding. This study aims to see how the effect of multirepresentational learning in improving conceptual understanding students at the University level.…”
Section: Introductionmentioning
confidence: 99%